THE USE OF ISLAMIC CASHLESS SOCIETY AS A COMMUNITY NEED IN THE NEW NORMAL PERIOD - Rahmayati Rahmayati; Frida Yanti Sirait (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to compare the use of a conventional and sharia-based cashless society in the new normal, cashless transactions that are considered more real time by the community. The research method used is qualitative, with library study data collection based on the use of cashless with digital wallets in Indonesia which people tend to use during the COVID-19 pandemic such as Shopee pay, Dana, Ovo, link aja, link aja sharia, gopay. The results showed that Go-Pay, OVO, DANA, LinkAja. Five products with the best developers from each. ShopeePay is 39%, OVO is 18%, Go-pay is 17%, Dana is 18%, and LinkAja is 9%, Shopeepay has succeeded in gaining public trust in transactions during the pandemic, while the LinkAja Syariah Service is the first Islamic electronic money. The conclusion of this research is Shopee pay is Cashless with the most popular ranking during the covid-19 pandemic, Shopeepay is also the main payment method that is in demand and used by the non-cash movement community.Keywords: Cashless; Islamic Cashless Society; New Normal